Analisis Efek Domino Covid-19 Terhadap Pertumbuhan Investor Pasar Modal di Sumatera Utara - Hardian Aditya Mingka; Fauzi Arif Lubis; Rahmat Daim Harahap (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2023)
The purpose of this study was conducted to determine the impact of the COVID-19 pandemic on the growth of capital market investors in North Sumatra and the factors that influence investor growth during the pandemic, thereby increasing the value of transactions in North Sumatra. By using qualitative research methods and using data obtained from the field, and data collected with various sources that are already available. This study is descriptive in nature with the aim of providing descriptive, methodical, actual and accurate explanations of the facts, characteristics, and relationships between the phenomena discussed. The result can be obtained that the domino effect of covid-19 in the health sector on the capital market sector is a decrease in the health level of investors aged more than 40 years, a decrease in public income, difficulties in education about the capital market directly, increasing public awareness of the importance of investing.